2016
DOI: 10.1016/j.ribaf.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Systemic risk of European financial institutions: Estimation and ranking by the Marginal Expected Shortfall

Abstract: The task of processing a systemic event and its negative externalities requires approaches to measure systemic risks and break it down into contributions of different institutions. The objective of this paper is to assess systemic risk in European banks during the period following the 2007 financial crisis. To do so, we estimated the systemic risk of a sample of 281 European institutions from January 01, 2006 to December 31, 2012. We used the Marginal Expected Shortfall (MES) to measure systemic risk. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 9 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Our study is further motivated by the fear that new systemic events at national level could trigger a new global crisis. The analysis builds on the recent literature that attempts to empirically measure systemic risk during the main systemic or high volatility episodes of the last decade (see, e.g., Acharya et al, 2017;Adrian and Brunnermeier, 2016;Bernal et al, 2014;Black et al, 2016;Brownlees and Engle, 2016;Derbali and Hallara, 2016). However, most of the existing literature is focused only on the Subprime and/or the Sovereign Debt crisis, and does not consider other episodes, such as China's recent stock market turbulence, which could have a severe systemic impact on the major global financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is further motivated by the fear that new systemic events at national level could trigger a new global crisis. The analysis builds on the recent literature that attempts to empirically measure systemic risk during the main systemic or high volatility episodes of the last decade (see, e.g., Acharya et al, 2017;Adrian and Brunnermeier, 2016;Bernal et al, 2014;Black et al, 2016;Brownlees and Engle, 2016;Derbali and Hallara, 2016). However, most of the existing literature is focused only on the Subprime and/or the Sovereign Debt crisis, and does not consider other episodes, such as China's recent stock market turbulence, which could have a severe systemic impact on the major global financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…The result shows that companies such as AIG, Lehman Brothers and Merrill Lynch, which suffered important losses during the financial crisis, are systemically important institutions. Derbali and Hallara (2015) used the MES model to measure the systemic risk of European financial institutions. Grieb (2015) applied the model of nonlinear factors, and logistic regression model to measure the potential impact of hedge funds on systemic risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Banulescu and Dumitrescu (2015) employed a component expected shortfall approach to evaluate the SIFIs, and found that the financial institutions labeled as SIFIs by the financial stability board are identified. Derbali and Hallara (2016) used the Marginal Expected Shortfall model to measure the systemic risk of financial institutions in European countries, and the results showed that the systemic risk supported by European banks have a high value. Haider et al (2018) utilized the SRISK model to evaluate the systemic risk contribution in Chinese SIFIs, and the results found that banks are the SIFIs during the global crisis.…”
Section: Introductionmentioning
confidence: 99%